PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK KASUR PADA PT. RIP - Hermansyah, Muhammad (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study is to examine the impact of seven elements of marketing mix (product, price, place, promotion, people, process and physical evidence) on customer satisfaction of mattress. Data were collected from 100 customers residing in South Jakarta using self-reporting questionnaires. Factor analysis is used to validate the instrument and regression analysis was used to test the hypotheses. The results of research on the marketing mix strategy applied at PT. RIP Suwayuwo. Research results from consumer responses can it is known that the product aspect with an average of 3.34 is in the very good category. Aspect price with an average of 3.13 in the good category. Aspects of place with an average of 3.21 in good category. The promotion aspect with an average of 2.48 in the poor category. The people aspect with an average of 3.45 is in the very good category. Process aspects with an average of 3.32 in the very good category. Physical evidence aspects with averages 3.13 in good category.